Pemberian Kolostrum dan ASI Eksklusif pada Bayi Baru Lahir - Nuril Absari; Choralina Eliagita; Mika Oktarina (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
Early breastfeeding initiation is one way for babies to get colostrum, colostrum is the first liquid secreted by the breast glands, one of the causes of low nutrition is the level of IMD including colostrum feeding, colostrum is an antibody that is ready to protect the baby when the baby's condition is very weak. Colostrum is given when the first milk comes out, after that it is transitional breast milk, breast milk is given to babies for 6 months without any additional food, and can be given for 2 years. Exclusive breastfeeding is the best supplementary food and is a natural nutrient that is needed in the process of growth and development of the baby. The provision of colostrum and exclusive breastfeeding is still relatively low due to many mothers who do not understand and lack of knowledge about colostrum and exclusive breastfeeding. The purpose of this community service is to provide information about the importance of giving colostrum and exclusive breastfeeding to newborns. The method used in this community service activity begins with the opening and introduction of the speakers, then continued with the delivery of counseling material about colostrum and exclusive breastfeeding, question and answer sessions to participants and finally closing. With this activity, it can increase the knowledge of mothers about the provision of colostrum at the time of the first milk discharge and the importance of exclusive breastfeeding until the age of 6 months.